New proposal for sugarcane vinasse treatment by hydrothermal carbonization: An evaluation of solid and liquid products - Fregolente, Laís G. [UNESP]; de Castro, Antonio J.R.; Moreira, Altair B. [UNESP]; Ferreira, Odair P.; Bisinoti, Márcia C. [UNESP] (Sociedade Brasileira de Quimica (SBQ), 2020)
Vinasse is a residue of ethanol production from sugarcane. In view of the problems associated with its disposal, this study aimed to propose a treatment for vinasse by hydrothermal carbonization. The influence of temperature (100 to 200 oC), acidity (1.7 to 8.3%) and reaction time (12 to 48 h) on the hydrothermal treatment was evaluated, as well the characteristics of the solid (hydrochar) and liquid (process water) products. For the solid product, two hydrothermal carbonization conditions stood out as leading to higher carbonization and yields. These conditions were 200 oC, 8.3% acidity and times of 12 and 48 h. For the process water, the carbonization reaction at 200 oC, 8.3% acidity and 48 h produced the highest discoloration and 77% reduction of total organic carbon. Thus, hydrothermal carbonization proved to be an efficient method to treat vinasse, and the hydrochar presents potential for use as fertilizers / soil conditioners, and also the process water after pre-treatment.
Keywords: Hydrochar; Hydrothermal carbonization; Process water; Reuse; Sugarcane